Fremdheitswahrnehmung schwarzafrikanischer Migranten bei Kum’a Ndumbe III. "Ich klopfte an deiner Tür…" - Koung A Sanama, Wilfried Emmanuel (Acta Neophilologica, 2023)
An increase of new migration movements is curbed on the one hand by sociopolitical barriers and security measures. On the other hand, those same security measures put in place to slow down the increase of migration’s growth seem to be inadequate. This poses the problem of coexistence between “natives” and “foreigners”. Political and scientific discourses are concerned with (the relation between) the increase of tremendous migration movements, which in turn interfere with the sociopolitical barriers. This article sees itself as a proposal for a stronger promotion of interculturally, openness, empathy and sensitivity towards ethnic minorities in majority societies. Moreover, it aims at deconstructing usual, negative images and ideas – as far as Black African migrants are concerned – in the media and scientific publications. It reinforces a negative climate for the phenomenon of “migration” in political debates. The concept of foreigners is to be applied here, after theoretical differentiations have been worked out. Based on the analysis of the genre mix Ich klopfte an deiner Tür… special aspects of perception of the disposition of “foreignness” and its literary representation are to be thoroughly examined. In other words, problems related to the experience of foreignness should be presented from the perspective of the concept of foreignness. The question thereof will be to know how the author Kum’a Ndumbe the Third (III) perceives the encounter of African migration figures with the German characters.